2016
DOI: 10.7554/elife.22502
|View full text |Cite
|
Sign up to set email alerts
|

Multiple alleles at a single locus control seed dormancy in Swedish Arabidopsis

Abstract: Seed dormancy is a complex life history trait that determines the timing of germination and is crucial for local adaptation. Genetic studies of dormancy are challenging, because the trait is highly plastic and strongly influenced by the maternal environment. Using a combination of statistical and experimental approaches, we show that multiple alleles at the previously identified dormancy locus DELAY OF GERMINATION1 jointly explain as much as 57% of the variation observed in Swedish Arabidopsis thaliana, but gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
78
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(81 citation statements)
references
References 59 publications
2
78
1
Order By: Relevance
“…DOG1 has previously been found to affect germination timing, flowering time and fitness in a seasonal field environment outside the native range (Chiang et al., ). The role of DOG1 in local adaptation is supported by the geographic distribution of DOG1 alleles and associated variation in primary seed dormancy (Kerdaffrec et al., ; Kronholm, Picó, Alonso‐Blanco, Goudet, & de Meaux, ; Postma & Ågren, ) and by geographic variation in DOG1 expression (Chiang et al., ). Taken together, the results suggest that variation in DOG1 and differences in seed dormancy play a key role in adaptive differentiation in A. thaliana by affecting timing of germination.…”
Section: Discussionmentioning
confidence: 99%
“…DOG1 has previously been found to affect germination timing, flowering time and fitness in a seasonal field environment outside the native range (Chiang et al., ). The role of DOG1 in local adaptation is supported by the geographic distribution of DOG1 alleles and associated variation in primary seed dormancy (Kerdaffrec et al., ; Kronholm, Picó, Alonso‐Blanco, Goudet, & de Meaux, ; Postma & Ågren, ) and by geographic variation in DOG1 expression (Chiang et al., ). Taken together, the results suggest that variation in DOG1 and differences in seed dormancy play a key role in adaptive differentiation in A. thaliana by affecting timing of germination.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the causative genes are sometimes located away from the GWAS peaks. This has been observed in a number of association studies in plants including Arabidopsis (Atwell et al ., ; Kerdaffrec et al ., ), rice (Huang et al ., , ; Yano et al ., ), sorghum (Lin et al ., ), and tomato (Lin et al ., ). This misleading association is called synthetic association (or ‘ghost association’), which is presumed to be caused by LD between common tagged markers and rare causative variants (Dickson et al ., ; Chang and Keinan, ).…”
Section: Synthetic Association: Misleading For Causalitymentioning
confidence: 99%
“…Subsequent studies have demonstrated that the seed dormancy function of DOG1 is conserved in many different plant species . Recent work has also shown that multiple independently evolved DOG1 alleles are responsible for the adaptation of Arabidopsis to local conditions, explaining the surprisingly high proportion of naturally occurring variability in dormancy .…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has also shown that multiple independently evolved DOG1 alleles are responsible for the adaptation of Arabidopsis to local conditions, explaining the surprisingly high proportion of naturally occurring variability in dormancy [7].…”
Section: Introductionmentioning
confidence: 99%